A machine learning model for predicting frequency of Low Power VCO considering process parameter variations - Sau, Tathagata; Ghosh, Sudipta; Pal, Krishna Kanta; Biswas, Sandan; Sarkhel, Saheli (2023 8th International Conference on Computers and Devices for Communication (CODEC), 2023)
A low-power CMOS Voltage Controlled Oscillator (VCO) becomes the subject of scrutiny, as LTspice simulations intertwine with machine learning finesse. This paper delves into the analysis of a low-power CMOS Voltage Controlled Oscillator (VCO) through LTspice simulations and machine learning techniques. Focusing on the VCO's behaviour under low-power conditions, a Linear Regression based machine learning model has been automated to accurately predict VCO's output frequency corresponding to process parameter variations of the constituent transistors.